2016
DOI: 10.1111/hdi.12457
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and integrating patient and caregiver perspectives for clinical practice guidelines on the screening and management of infectious microorganisms in hemodialysis units

Abstract: Patients and caregivers emphasized the need for guidelines to address patient education and engagement, and the psychosocial implications of communication and provision of care in the context of infectious microorganisms in hemodialysis units. Integrating patient and caregiver perspectives can help to improve the relevance of guidelines to enhance quality of care, patient experiences, and health and psychosocial outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…A facilitated workshop with 11 participants (patients ( n = 8), caregivers ( n = 3)) was conducted to identify and discuss potential topics for inclusion in the guidelines. The full methodology and results of patient involvement in the development of this guideline have been published separately …”
Section: Methodsmentioning
confidence: 99%
“…A facilitated workshop with 11 participants (patients ( n = 8), caregivers ( n = 3)) was conducted to identify and discuss potential topics for inclusion in the guidelines. The full methodology and results of patient involvement in the development of this guideline have been published separately …”
Section: Methodsmentioning
confidence: 99%
“…None of the facilitators were involved in the clinical care of the patients. The question guide was developed based on previous KHA‐CARI workshops and discussion with the research team. Participants were asked to discuss their experiences with percutaneous renal biopsy, and to suggest topics and outcomes they considered important to include in the new guideline.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, work began by Kidney Health Australia – Caring for Australasians with Renal Impairment (KHA‐CARI) to develop a guideline for renal biopsy following standard processes for evidence‐based guideline formulation . As is routine for KHA‐CARI guidelines, patient and caregiver involvement is structured though a parallel process to ensure that the guideline scope and recommendations explicitly address patients’ priorities . This study aims to identify topics and outcomes relating to renal biopsy that are important to patients with kidney disease and caregivers to be included in the KHA‐CARI guideline; to describe the reasons for their choices; to compare topics and outcomes identified by patients/caregivers with those selected by the expert working group; and to discuss the process of integrating patient and caregiver feedback into the guideline.…”
mentioning
confidence: 99%
“…Yet, it stands to reason that these individuals who spend much of their time receiving healthcare can contribute to positive outcomes in their own care and for other patients in their facility. Limited studies or evaluations incorporating patient opinions have demonstrated that patients view infections as important adverse events and many wish to become involved to help ensure the safety and quality of care they receive (34,35). Although CDC suggests some topic areas for patient education (vascular access care, hand hygiene, risks related to catheter use, recognizing signs of infection, and instructions for access management when away from the dialysis unit), the best means of engaging patients in clinic infection prevention activities is unknown.…”
Section: Interventions and Additional Evidence Of Effectivenessmentioning
confidence: 99%